Microfluidic analysis of electrokinetic streaming potential induced by microflows of monovalent electrolyte solution - Chun, MS; Lee, TS; Choi, NW (IOP PUBLISHING LTD, 2005)
We develop a theoretical model of the electrokinetic streaming potential considering the Navier-Stokes equation coupled with the Poisson-Boltzmann equation in order to elaborate the possible applicability of the microfluidic-battery from conceptualization to system validation. The ion transport in the microchannel is described on the basis of the Nernst-Planck equation. In this study, monovalent symmetric electrolytes are considered, and the profile of fluid conductivity is derived in terms of both the concentration profile and the mobilities of anions and cations. The present simulations provide that the flow-induced streaming potential increases with increasing surface potential of microchannel wall, whereas increasing the surface conductivity reduces the streaming potential. We also present the results on the change of streaming potential with variations of the electric double layer thickness normalized by the channel radius. It is of interest to find the behavior that a lower value of ion mobility leads to the enhancement of streaming potential, which tends to develop with either increasing bulk electrolyte concentration or decreasing surface conductivity. Hence, a choice of electrolyte should be considered to obtain improved performance.
Keywords: CAPILLARY-ELECTROPHORESIS; FLOW; MICROCHANNELS; FILTRATION